The influence of humidity and immersion temperature on the properties and failure mode of PBT-GF30/silicone bonded joints. (1st June 2022) - Brandão, R.; Borges, C.S.P.; Marques, E.A.S.; Carbas, R.J.C.; Akhavan-Safar, A.; Schmid, F.; Ueffing, C.; Weißgraeber, P.; da Silva, L.F.M.
Abstract: The housing of automotive electrical components are commonly manufactured from polybutylene terephthalate with 30% of glass fiber (PBT-GF30). These housings can be subjected to severe conditions of temperature and humidity that can catalyze the degradation of their properties. In order to connect the different parts of the housing, a silicone adhesive is used, which also serves as a sealant preventing moisture from entering the final component. Therefore, to understand if the joint serves its purpose correctly, the effects of temperature and water uptake in joints with PBT-GF30 substrates and silicone adhesive were studied. Single lap joints (SLJ) and double cantilever beam (DCB) joints were tested at three different temperatures (70, 90 and 130 °C) and in three different conditions (dried, aged in water and dried after aging). To understand if water immersion introduced irreversible damage to the joints, the re-dried condition was also analyzed. The tensile properties of the bulk substrate and adhesive for all conditions were also determined. It has been seen that, generally, since the adhesive has a higher strength when aged, this leads to a better joint performance at this condition. However, at 90 °C and 130 °C there was chemical degradation of the PBT-GF30 after aging, which lead to failure approaching the substrate in those conditions for the SLJ. This was attributed to the release of chemical compounds that stay at the adhesive/substrate interface. In the DCB, since the loading of the substrate is even more severe, there was substrate failure. Finally, a numerical model was created for all conditions tested, which showed that the joints can be simulated by the properties of the bulk adhesive and substrate, showing that the effect of the interface is not preponderant.